2016
DOI: 10.1542/peds.2016-2195
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Medication Treatment of Pediatric Hypertension: A Retrospective Cohort Study

Abstract: Hypertension and prehypertension were infrequently diagnosed among pediatric patients. Guidelines for diagnosis and initial medication management of abnormal BP in pediatric patients are not routinely followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 29 publications
8
39
1
4
Order By: Relevance
“…Unlike these other common conditions, however, abnormal BP is commonly unrecognised and untreated by primary care providers. In a large study utilising electronic medical record data, Kaelber and colleagues (7) demonstrated that just 10.2% of children who met criteria for elevated BP and 23.2% of those who met criteria for HTN had that diagnosis documented in their medical record, confirming the results of prior single-centre studies (8,9). Treatment rates in those actually diagnosed with HTN were surprisingly low, with just 5.6% of patients receiving antihypertensive medications (7).…”
Section: Key Notesmentioning
confidence: 76%
See 2 more Smart Citations
“…Unlike these other common conditions, however, abnormal BP is commonly unrecognised and untreated by primary care providers. In a large study utilising electronic medical record data, Kaelber and colleagues (7) demonstrated that just 10.2% of children who met criteria for elevated BP and 23.2% of those who met criteria for HTN had that diagnosis documented in their medical record, confirming the results of prior single-centre studies (8,9). Treatment rates in those actually diagnosed with HTN were surprisingly low, with just 5.6% of patients receiving antihypertensive medications (7).…”
Section: Key Notesmentioning
confidence: 76%
“…While the conclusions of the USPSTF have been subject to a great deal of criticism , they provide a context for the data mentioned earlier regarding low rates of recognition and treatment of childhood primary HTN . Since there are no prospective trials linking childhood BP levels and later CV disease, the impetus for treatment is diminished, creating an overall ambivalence regarding HTN in the young.…”
Section: Lack Of Cardiovascular Outcome Data Creates Provider Ambivalmentioning
confidence: 99%
See 1 more Smart Citation
“…This figure rose to 75% with the inclusion of patients whose BP were rechecked and remained elevated, and again did not receive any intervention or follow-up. Kaelber  et al ’s recent retrospective cohort study of 398 079 patients aged 3–18 years also reiterates the infrequency of a diagnosis of paediatric hypertension 58. Only 23% and 10.2% of hypertensive and prehypertensive patients were formally diagnosed as such, and of those with persistent hypertension for 12 months or longer a mere 5.6% were prescribed medication.…”
Section: Screening For High Bpmentioning
confidence: 95%
“…However, the percentile‐based definition included hundreds of abnormal BP cutoff values, which resulted in a complex and cumbersome decision process. Elevated BP in children and adolescents was frequently undiagnosed in the clinical practice . As a solution for this problem, the American Academy of Pediatrics (AAP) recommended 120/80 mm Hg as thresholds to identify elevated BP in adolescents aged 13‐17 years .…”
Section: Introductionmentioning
confidence: 99%